Cryptococcus neoformans Meningoencephalitis in an Immunocompetent Patient after COVID-19 Infection - Hebah Ghanem; Geetha Sivasubramanian (Case Reports in Infectious Diseases)
Cryptococcus neoformans is a saprophytic fungus that causes fatal disseminated infections in immunocompromised hosts. Since the onset of the COVID-19 pandemic, multiple cases of secondary viral, bacterial, and fungal infections have been reported in patients after SARS-CoV-2 infection. We describe here a case of severe cryptococcal meningitis that developed in a previously healthy patient one week after treatment of SARS-CoV-2 infection with dexamethasone. This case adds to the growing knowledge of emerging secondary infectious complications including opportunistic pathogens after SARS-CoV-2 infection. While few reports allude to depressed T-cell function and lymphopenia due to SARS-CoV-2 infection, further studies are needed to evaluate the effects of this infection and its treatment on the immune system and its contribution to the emergence of secondary opportunistic infections.